2020
DOI: 10.1002/ejoc.202001203
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and Scalable Synthesis of Carba‐α‐d‐Glucosamine

Abstract: An efficient, high‐yielding synthesis of carba‐α‐d‐glucosamine is reported. Key features of this optimized route include an innovative protecting group strategy and an unusual, stereoconvergent Ferrier carbocyclization of a hindered substrate. The sequence enables the synthesis of larger amounts of this structurally novel antibiotic to allow more detailed biological evaluations of its unique mode of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the following four decades, the chemical, biological, and conformational aspects of carbasugars were extensively studied [12,13], resulting in studies on enzyme inhibition, lectin-binding, and even HIV and cancer treatment [14][15][16]. Various strategies have been employed for the synthesis and isolation of carbasugars, mostly starting from simple monosaccharides such as glucosamine and resulting in the corresponding carbasugars [17][18][19]. Other approaches work from simple hexopyranoses to more complex carbafuranoses such as carbaarabinofuranosides [20,21] or even more complex carbasugar derivatives such as fluorinated carbasugars [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following four decades, the chemical, biological, and conformational aspects of carbasugars were extensively studied [12,13], resulting in studies on enzyme inhibition, lectin-binding, and even HIV and cancer treatment [14][15][16]. Various strategies have been employed for the synthesis and isolation of carbasugars, mostly starting from simple monosaccharides such as glucosamine and resulting in the corresponding carbasugars [17][18][19]. Other approaches work from simple hexopyranoses to more complex carbafuranoses such as carbaarabinofuranosides [20,21] or even more complex carbasugar derivatives such as fluorinated carbasugars [22].…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been employed for the synthesis and isolation of carbasugars, mostly starting from simple monosaccharides such as glucosamine and resulting in the corresponding carbasugars [ 17 19 ]. Other approaches work from simple hexopyranoses to more complex carbafuranoses such as carbaarabinofuranosides [ 20 , 21 ] or even more complex carbasugar derivatives such as fluorinated carbasugars [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, an efficient, highyielding synthesis of α-D-carba-glucosamine (CGlcN) was reported that allowed the biological evaluations of its mode of action as an glucosamine analog. [2][3][4][5] In B. subtilis, CGlcN is taken up and concomitantly phosphorylated, like the natural metabolite, via the glucosamine-specific PTS system GamP, gaining intracellularly CGlcN-6-phosphate (CGlcN6P). 3 Due to impaired acetal chemistry CGlcN6P cannot be deamidated via the glucosamine deamidase (NagB) such as the carbohydrate counterpart glucosamine-6-phosphate (GlcN6P).…”
mentioning
confidence: 99%